Comparative evaluation of BACTEC FX, BacT/ALERT 3D, and BacT/ALERT VIRTUO automated blood culture systems using simulated blood cultures. Issue 1 (2nd January 2022) - Li, Zhengkang; Liu, Suling; Chen, Huimin; Zhang, Xinqiang; Ling, Yong; Zhang, Ni; Hou, Tieying
ABSTRACT: Background: To evaluate the performance of BACTEC FX, BacT/ALERT 3D, and VIRTUO systems using simulated blood culture (BC). Methods: Two experimental designs based on 'with' or 'without' added trough antibiotic concentrations in bottles were implemented. Results: For the experiment A, A shorter time to detection (TTD) was observed for most of organisms (17/22) in VIRTUO system. VIRTUO system was also faster than 3D and FX systems no matter in aerobic and anaerobic bottles. The anaerobic bottles had faster detection than aerobic bottles in 3D system (13.68 h vs 15.36 h, P < 0.001) and VIRTUO system (10.30 h vs 12.46 h, P = 0.001) but not in FX system ( P = 0.38). When antibiotics were present, the bacterial recovery rate (RR) of FX, 3D and VIRTUO systems were 64.10% (50/78), 58.97% (46/78) and 43.59% (34/78), respectively ( P = 0.027). the bacterial RR of various bottles were as follows: BPA vs. FA vs. SA [84.44%(38/45) vs. 55.56%(25/45) vs. 42.22(19/45), P < 0.001]; BFN vs. FN vs. SN [36.36%(12/33) vs. 63.64%(21/33) vs.45.45%(15/33), P = 0.078]. Conclusions: The VIRTUO system allowed faster growth detection for most of organisms compared with FX and 3D systems. When antibiotics were present, the bottles containing antibiotic-binding agent showed better bacterial RR, especially in BACTEC Plus Aerobic/F bottles.